Quality of Lemongrass-Pandan Stew with Added Lime (Citrus amblycarpa) as Herbal Drink - Suharti Suharti; Suko Priyono; Lucky Hartanti (FoodTech: Jurnal Teknologi Pangan, 2023)
Herbal drinks are drinks made from natural ingredients that are beneficial to the body and are believed to have traditional healing properties. Herbal drinks are usually made from spices or from the plant itself such as roots, stems, leaves, flowers or tubers. The plants used are very easy to find, especially in Pontianak, West Kalimantan, one of which is lemongrass, pandan leaves and lime chili. In addition to the needs of the kitchen, chili orange is a source of vitamin C which is beneficial for the body and orange chili juice also gives a distinctive taste and color to food and drinks. The purpose of this study was to determine the quality of lemon grass pandan herbal drink by adding chili orange juice as a herbal drink to produce the best physicochemical and sensory properties. The method used was a randomized block design (RBD) with 7 treatment levels (p) and 4 replications for a total of 28 treatments. The results showed that the best treatment based on the effectiveness index of lemon grass pandan herbal drink with the addition of orange chili sauce was (4:30:30:40) with the characteristics of pH 3.79, vitamin C 45.76 mg/100g, TPT 5.00 ºBrix. Sensory char